Transfer of ascription in a church sui iuris with particular application to the archdiocese of Alba-Iulia, Romania. - Nagy, Laszlo. (University of Ottawa (Canada), 2001)
Prior to the Second Vatican Council, and even in the years immediately following, there was confusion in the Church regarding the meaning of the term "rite". In many instances, the official documents used the word in the sense of a Church itself; but, in others, the term referred principally to the various ceremonies and liturgical practices. Vatican II intended to apply the expression "Particular Church" to the Churches sui iuris existing in the East (a number of which comprised many Metropolinates and eparchies), but this was not in accordance with its use in other documents where the expression referred to a diocese or the equivalent. Various compromises in vocabulary were attempted. Yet, it was only with the promulgation of the Codex canonum Ecclesiarum orientalium in 1990 that the terminology was clarified. To illustrate this point, the expression "transfer of rite" can be considered. While previously, the expression referred to a transfer of membership in a Church sui iuris, according to the 1990 legislation, the correct expression would now be "transfer of membership". The norms governing transfer of membership are examined in detail, comparing the canons of the 1983 Code of Canon Law with those of the 1990 Oriental Code. There are significant differences. Because of the vicissitudes of history affecting Romania, the Latin Archdiocese of Alba-Iulia has experienced serious difficulties in determining the status of membership of many of the faithful who often changed adherence according to the political situation. To explain this, we must recall that Transylvania was part of Hungary; later, following the two World Wars, certain parts were annexed to Romania. An overview of the various facts leading to this complicated situation and papal and curial efforts to help clarify issues relating to membership are noted. In the final chapter of the dissertation, a number of practical issues are examined, keeping in mind their eventual relevance to the Archdiocese of Alba-Iulia. However, we must recognize at times that it is not only a question of law. The personalities involved sometimes influence the way in which the law is applied. The various calls to cooperation and inter-Church activity found in official Church documents are noted, more particularly, Pope John Paul II's Apostolic Letter for the third centenary of the union of the Greek-Catholic Church of Romania with the Church of Rome, May 7, 2000. The study concludes by noting that something must be done to respect the wishes of various Catholics who, in recent times, have transferred membership for a number of reasons (not all of which are recognized as canonically valid today), but who nevertheless are living in a somewhat ambiguous situation. Some points for future clarification are noted.
Keywords: Religion, General.